1978
DOI: 10.1128/aac.14.3.444
|View full text |Cite
|
Sign up to set email alerts
|

Flavobacterium meningosepticum Meningitis: Report of Selected Aspects

Abstract: Two patients developed meningitis due to Flavobacterium meningosepticum. Because of resistance to most available antimicrobial agents, intravenous and intraventricular erythromycin was administered to one patient. Subsequent development of resistance to erythromycin prompted the use of intravenous and intraventricular rifamycin, which eventually resulted in cure. Diagnosis of F. meningosepticum meningitis in the second patient was delayed, and appropriate therapy was not administered until 4 days prior to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Meningitis seems to be the most severe type of Flavobacterium infection [2,5,12,[14][15][16]25,30] with four of eight patients dying from this opportunistic disease (Table 5). All patients had significant underlying disease (including tuberculosis in two), and most had circumstantial evidence as to how the organism could have gained access to the meninges (including a recent sterile lumbar puncture in two and rinorrhea in two).…”
Section: Discussionmentioning
confidence: 99%
“…Meningitis seems to be the most severe type of Flavobacterium infection [2,5,12,[14][15][16]25,30] with four of eight patients dying from this opportunistic disease (Table 5). All patients had significant underlying disease (including tuberculosis in two), and most had circumstantial evidence as to how the organism could have gained access to the meninges (including a recent sterile lumbar puncture in two and rinorrhea in two).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment was complemented with intramuscular RIF at 20 mg/kg every 12 h. Transient jaundice was a noted side effect, with ventricular antibiotic concentrations evaluated 20 to 24 h post-administration [ 119 ]. Further reports highlighted a treatment regimen consisting of concurrent intravenous RIF at 40 mg/kg per day and IVT-RIF at 5 mg daily for 22 days, resulting in CSF sterilization without reported adverse effects or toxicity [ 120 ]. An evaluation of nine meningitis cases treated with either IT or IVT-RIF at 3 mg/kg/day for a minimum of 10 days showed that five patients achieved CSF sterilization and survival.…”
Section: Resultsmentioning
confidence: 99%
“…RIF: In seven published literature, IT/IVT-RIF was given at doses of 2–5 mg for 7–50 days in seven studies. This regimen proved highly effective, especially in complex cases and when oral drugs failed, with no significant side effects [ 22 , 23 , 106 , 120 , 121 , 122 , 123 ]. The targeted concentration of RIF in the CSF was 15 mg/L.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations